11y-6y-13=55.90

Simple and best practice solution for 11y-6y-13=55.90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11y-6y-13=55.90 equation:


Simplifying
11y + -6y + -13 = 55.90

Reorder the terms:
-13 + 11y + -6y = 55.90

Combine like terms: 11y + -6y = 5y
-13 + 5y = 55.90

Solving
-13 + 5y = 55.90

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 5y = 55.90 + 13

Combine like terms: -13 + 13 = 0
0 + 5y = 55.90 + 13
5y = 55.90 + 13

Combine like terms: 55.90 + 13 = 68.9
5y = 68.9

Divide each side by '5'.
y = 13.78

Simplifying
y = 13.78

See similar equations:

| 6-24x+36y=0 | | -25+3x=-2x | | 11x-9-5=10x-4+3x | | 4x+5x-42=70-5x | | 15x=4/10 | | (x-5)+17=-3 | | 2tsp=XmL | | 38-4x=12+9x | | 42-n=28 | | -11=3+7x | | b-3+4b=-7+4b | | 3/5+2x=2/5 | | 4(x+18)=-2(x-6) | | -11X+6Y=-13 | | 2w-15w-18=-83 | | 13y-10y=9 | | (2xy-y)(2xy-y)= | | 46q-34=54q-82 | | 1/4x+3=17 | | (n/8)-3=-11 | | -7(1+7r)-6=379 | | s^2+8s-9=0 | | 125m-75m+43875=46125-175m | | 2x+3(-8)=0 | | 15x-2.4x=0.6+7.6x | | -4(x)-2y=-12 | | 25p^2-4=0 | | 5x=40*0.5 | | a=h(b+c)solve(b) | | 2x+5(x-1)= | | 3(-11)[5(-3)-7(-2)]= | | 6xrqw+13xrqw=133 |

Equations solver categories